Single institutional experience of management of penetrating trauma chest - Jadhav, Niranjan Ulhasrao; Pramanik, Subrata; Munjal, Ridhika; Gupta, Anubhav; Mathur, Anirudh; Kesharwani, Peeyush (International Surgery Journal, 2021)
Chest trauma is now the second most common non-intentional traumatic injury. Chest trauma is associated with high mortality. Control of blood loss and stabilization of vital organs is of vital importance over diagnostic and therapeutic measures. Bleeding may arise from chest wall, intercostal or internal mammary arteries, great vessels, mediastinum, myocardium, lung parenchyma, diaphragm or abdomen. Modified early warning signs (MEWS) score of >9 on presentation have shown higher rate of mortality. Diagnostic modalities such as extended-focused assessment with sonography in trauma (eFAST) have been effective. The type of surgical approach alters according to the site of injury. We here presented our experience with six such patients. All the six patients involved in this study had penetrating trauma chest with various sharp weapons including dagger, ice pick, flag post. Time of presentation of all these patients were delayed due to ours being a tertiary centre. The patients were explored on the basis of eFAST findings, intercostal drainage, hemodynamics. Out of the six patients two patients succumbed and the patients who died also had high MEWS score. All the patients were approached surgically with respect to the type of injury sustained. Penetrating chest trauma present a challenging clinical situation which warrants early evaluation and intervention. The cases of chest trauma then be it blunt or penetrating should always be treated within the advanced trauma life support (ATLS) guidelines followed by the definitive management. Regardless of any penetrating object, the foreign body should be left in situ and only to be removed under vision. If in case the penetrating object has already been removed the operative intervention is decided on the amount of drainage. With blunt chest trauma, approximately 15% of the deaths result directly from intrathoracic injury, but with penetrating chest trauma, nearly 100% of the deaths result from intrathoracic injury. Hence, the operative exploration of the chest in penetrating chest trauma and should be done on emergent basis as the mechanism of injury, vital organ damage and hemodynamic status all equate to higher rate of mortality.